The Effect of Fermentation Duration on Nutrition Composition of Seaweed (Sargassum sp.) Liquid Organic Fertilizer - Zakaria Zakaria; Andi Adam Malik; Khairuddin Khairuddin; Muhammad Ishak (Department of Aquaculture, 2023)
This study aims to determine the effect of fermentation duration on the nutrient composition of seaweed liquid organic fertilizer (Sargassum sp). This research was conducted from May to June 2017 at The University of Muhammadiyah Parepare. Test materials used in the form of seaweed and lactobacillus. The container used in the implementation of this research is 6 bottles of 1000 ml size, before the bottles are used first the bottles are washed clean. Then each bottle is filled with extracts of Sargassum sp. as much as 800 ml and 40 ml of probiotics. Two bottles of treatment A (without fermentation), 2 bottles for treatment B (7 days fermentation), 2 bottles for treatment C (14 days fermentation). The design was a completely randomized design (CRD) with 3 types of each treatment. The results showed that micro nutrients that the iron (Fe) were obtained highest in treatment C (concentration 162 ppm), Silica (Si) in treatment A (100 ppm), manganese (Mn) in treatment B (29 ppm). For the highest macro nutrients potassium (K) obtained in treatment C (concentration 0.52%), Calcium (Ca) in treatment B (0.33%), Sulfur (S) in treatment C (0.31%) , Chlorine (Cl) in treatment C (concentration 0.27%). The research concludes that the length of time of fermentation affects the nutrient content of liquid organic fertilizer seaweed.